2014
DOI: 10.1509/jmr.12.0090
|View full text |Cite
|
Sign up to set email alerts
|

Limited Availability Reduces the Rate of Satiation

Abstract: In general, consumers enjoy products less with repeated consumption. Unfortunately, there are few known ways to slow such satiation. The authors show that consumers satiate more slowly on a product when it is available for consumption only at limited times. Specifically, they find that perceived limited availability made a product more enjoyable, and yet this effect largely emerged only after repeated consumption. The authors attribute this finding to an urge to take advantage of a rare consumption opportunity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
59
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 90 publications
(72 citation statements)
references
References 38 publications
5
59
1
2
Order By: Relevance
“…Additional work identifying specific aspects of heterogeneity between early and late adopters that seeks to derive specific strategic implications for firms will help to move this stream of literature from a curiosity to an important strategic consideration. One example is the notion of consumer satiation (McAlister 1982, Sevilla andRedden 2014), with the idea that early adopters may become satiated by any given game (and seek out additional games) more rapidly than later adopters, which would correlate with our empirical results in this study. Exploring whether such satiation patterns are valid would be an interesting extension of the research on early versus late adopters.…”
Section: Discussionsupporting
confidence: 65%
“…Additional work identifying specific aspects of heterogeneity between early and late adopters that seeks to derive specific strategic implications for firms will help to move this stream of literature from a curiosity to an important strategic consideration. One example is the notion of consumer satiation (McAlister 1982, Sevilla andRedden 2014), with the idea that early adopters may become satiated by any given game (and seek out additional games) more rapidly than later adopters, which would correlate with our empirical results in this study. Exploring whether such satiation patterns are valid would be an interesting extension of the research on early versus late adopters.…”
Section: Discussionsupporting
confidence: 65%
“…Consistent with the stress produced by uncertainty, cues of economic uncertainty have been shown to increase people's consumption of food, especially snacking on high‐calorie foods (Laran & Salerno, ; Sevilla & Redden, ).…”
Section: How Financial Constraints Influence Consumer Behaviormentioning
confidence: 95%
“…An emerging stream of research on the determinants of satiation has also shown that enjoyment over time is influenced by contextual and psychological considerations that may have been present at the moment of consumption. Such influences may include the way in which a stimulus is categorized (Redden, 2008) or perceived (Sevilla & Redden, 2014), and any emotional or identity related considerations (e.g., Chugani et al, 2015;Poor et al, 2012;Yang & Galak, 2015).…”
Section: The Nature Of the Satiation Process And Its Influence On Recmentioning
confidence: 99%